A conserved Toll-like receptor-to-NF-κB signaling pathway in the endangered coral Orbicella faveolata. (February 2018) - Williams, Leah M.; Fuess, Lauren E.; Brennan, Joseph J.; Mansfield, Katelyn M.; Salas-Rodriguez, Erick; Welsh, Julianne; Awtry, Jake; Banic, Sarah; Chacko, Cecilia; Chezian, Aarthia; Dowers, Donovan; Estrada, Felicia; et al.
Abstract: Herein, we characterize the Toll-like receptor (TLR)-to-NF-κB innate immune pathway of Orbicella faveolata (Of), which is an ecologically important, disease-susceptible, reef-building coral. As compared to human TLRs, the intracellular TIR domain of Of-TLR is most similar to TLR4, and it can interact in vitro with the human TLR4 adapter MYD88. Treatment of O. faveolata tissue with lipopolysaccharide, a ligand for mammalian TLR4, resulted in gene expression changes consistent with NF-κB pathway mobilization. Biochemical and cell-based assays revealed that Of-NF-κB resembles the mammalian non-canonical NF-κB protein p100 in that C-terminal truncation results in translocation of Of-NF-κB to the nucleus and increases its DNA-binding and transcriptional activation activities. Moreover, human IκB kinase (IKK) and Of-IKK can both phosphorylate conserved residues in Of-NF-κB in vitro and induce C-terminal processing of Of-NF-κB in vivo . These results are the first characterization of TLR-to-NF-κB signaling proteins in an endangered coral, and suggest that these corals have conserved innate immune pathways. Highlights: A Toll-like receptor to NF-κB pathway is present in the coral Orbicella faveolata. Activities of O. faveolata TLR and NF-κB proteins are characterized. LPS treatment of coral tissue activated an NF-κB gene expression profile.